Answer and step-by-step explanation:
To make the general term of the given sequence, find the common difference first by subtracting a term by the previous term.
-5 - (-2) = -3
-8 - (-5) = -3
-11 - (-8) = -3
Thus, the common difference is -3.
Then use the first term and the common difference to form the general term.
[tex]an = - 2 + (n - 1) (- 3)[/tex]
To check if the general term is correct, let's try to find the second term which is already in the given sequence.
a2 = -5
a2 = -2 + (2 - 1)(-3)
a2 = -2 + (1)(-3)
a2 = -2 + -3
a2 = -5
-5 = -5
Therefore, the general term is correct.